2018
DOI: 10.1007/s10482-018-1049-1
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for cultivable Micromonospora strains in soils of the Atacama Desert

Abstract: Innovative procedures were used to selectively isolate small numbers of Micromonospora strains from extreme hyper-arid and high altitude Atacama Desert soils. Micromonosporae were recognised on isolation plates by their ability to produce filamentous microcolonies that were strongly attached to the agar. Most of the isolates formed characteristic orange colonies that lacked aerial hyphae and turned black on spore formation, whereas those from the high altitude soil were dry, blue-green and covered by white aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…In recent times innumerable filamentous actinobacteria have been isolated from desert soils and assigned not only to the ubiquitous genus Streptomyces but also to rare and poorly studied taxa, such as the genera Actinomadura, Amycolatopsis, Nocardiopsis, Nonomuraea, Saccharopolyspora and Saccharothrix (Okoro et al ; Goodfellow et al ). The application of cutting edge taxonomic and screening methods, especially those based on whole‐genome sequence data; show that such filamentous actinobacteria are a significant source of novel specialized metabolites (Bull et al ; Carro et al ; Carro et al ). In this context, especially gifted isolates from Atacama Desert habitats have been classified as novel species of Streptomyces , such as Streptomyces asenjonii (Goodfellow et al ), Streptomyces deserti (Santhanam et al ), Streptomyces atacamaensis (Santhanam et al ), Streptomyces bullii (Santhanam et al ) and Streptomyces leeuwenhoekii (Busarakam et al ).…”
Section: Desertsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times innumerable filamentous actinobacteria have been isolated from desert soils and assigned not only to the ubiquitous genus Streptomyces but also to rare and poorly studied taxa, such as the genera Actinomadura, Amycolatopsis, Nocardiopsis, Nonomuraea, Saccharopolyspora and Saccharothrix (Okoro et al ; Goodfellow et al ). The application of cutting edge taxonomic and screening methods, especially those based on whole‐genome sequence data; show that such filamentous actinobacteria are a significant source of novel specialized metabolites (Bull et al ; Carro et al ; Carro et al ). In this context, especially gifted isolates from Atacama Desert habitats have been classified as novel species of Streptomyces , such as Streptomyces asenjonii (Goodfellow et al ), Streptomyces deserti (Santhanam et al ), Streptomyces atacamaensis (Santhanam et al ), Streptomyces bullii (Santhanam et al ) and Streptomyces leeuwenhoekii (Busarakam et al ).…”
Section: Desertsmentioning
confidence: 99%
“…Similarly, novel dereplicated isolates belonging to less well‐known genera have been validly named, as exemplified by Amycolatopsis vastitatis (Idris et al ), Lentzea chajnantorensis (Idris et al ) and Pseudonocardia nigra (Trujillo et al ). The genomes of some of these isolates have the capacity to synthesize many novel specialized metabolites and contain stress‐related genes that provide an insight into how actinobacteria adapt to the extreme environmental conditions found in Atacama Desert habitats (Idris et al ; Carro et al ).…”
Section: Desertsmentioning
confidence: 99%
“…Amongst actinobacteria, micromonosporae are second only to streptomycetes in their ability to synthesize natural products, notably antibiotics, including ones that are not only in clinical use [32] but considered essential to global health [91]. Interestingly, the application of innovative selective isolation procedures has shown that micromonosporae are a feature of diverse Atacama Desert soils [92].…”
Section: Is Biogeography a Roadmap To Drug Discovery?mentioning
confidence: 99%
“…Complementary metagenomic surveys of Atacama Desert habitats have revealed an enormous actinobacterial diversity most of which went undetected in corresponding culture-dependent studies 24,25 . Improved selective isolation and growth procedures can be expected to address this disparity between culture-dependent and culture-independent data, as illustrated by the discovery that members of the genus Micromonospora can be isolated from Atacama Desert soils 26 . This is an interesting development as micromonosporae are second only to streptomycetes as a source of new specialised metabolites 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…The present study was designed to establish the taxonomic provenance of five Micromonospora strains isolated from an extreme hyper-arid Atacama Desert soil with a particular focus on their biotechnological and ecological potential. The isolates are known to be genetically diverse and four of them, namely LB4, LB39 T and LB19 and LB32 T , were found to be most closely related to the type strains of Micromonospora chalcea 32,33 , the type species of the genus, Micromonospora chokoriensis 34 and Micromonospora saelicesensis 35 , respectively, based on 16S rRNA gene sequence similarities 26 . The isolates and their closest phylogenetic neighbours were the subject of an extensive polyphasic taxonomic study which showed that isolates LB32 T and LB39 T represent new Micromonospora species for which the names Micromonospora arida and Micromonospora inaquosa are proposed.…”
Section: Introductionmentioning
confidence: 99%